ADAPTIVE COPING AMONG BLACK FAMILY CAREGIVERS OF PERSONS WITH DEMENTIA: A PILOT STUDY - Robinson-Lane, S (Innov Aging, 2018)
Family caregivers of Black older adults with Alzheimer’s disease and/or related dementia (ADRD) have an increased risk of developing dementia due to both hereditary and stress related risk factors. Furthermore, caregivers often experience significant emotional and physical health challenges that can diminish satisfaction with caregiving and reduce their ability to provide assistance. Thus, there is a need for culturally responsive support programs that help Black ADRD caregivers to effectively manage their own health and use their preferred ways of coping to manage care-related stress. To this end, a descriptive study of Black ADRD caregivers that evaluates the frequency of use of particular coping strategies and the relationships between those strategies and selected health and quality of life outcomes is necessary. The present pilot study evaluated process outcomes and feasibility of the proposed work. Twenty family caregivers of persons with dementia, who self-identified as Black or African American, completed a survey comprised of a demographic questionnaire, various measures of function, caregiving self-efficacy, social support, coping, and positive aspects of caregiving. In addition to completing descriptive statistics, Spearman correlation coefficients were used to identify relationships between variables. The adaptive coping strategies most frequently used by those in the sample (n=20) included: taking strength from spirituality (80%), using past experiences (80%), and information gathering (75%). Significant correlations were found between being effective under stress and positive health outcomes (physical health p=0.04, mental health p=0.01). The proposed survey measures provided minimal participant burden and may be effectively used to develop a conceptual model.